2007
DOI: 10.1088/0957-4484/18/22/225705
|View full text |Cite
|
Sign up to set email alerts
|

Photoelastic effect in ZnO nanorods

Abstract: A novel phenomenon called the photoelastic effect had been observed in ZnO nanorods, along with a number of intriguing anomalies. With increasing excitation power, it was found that the A 1 (LO) phonon exhibited a red-shift in frequency, on top of a blue-shift in the photoluminescence (PL) peak energy. In addition, the temperature-dependent photoluminescence spectra behaved quite differently under high and low excitation power. All our results can be accounted for by the photoelastic effect, in which the built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…It has wide and direct band gap (3.37 eV), [13][14][15] and its large exciton binding energy (60 meV). [16][17][18][19] Hence, it has potential application as n-and p-type window layers in organic solar cells due to their excellent physical properties. 5,6 Organic solar cells have attracted much attention because of their low cost and high e±ciency.…”
Section: Introductionmentioning
confidence: 99%
“…It has wide and direct band gap (3.37 eV), [13][14][15] and its large exciton binding energy (60 meV). [16][17][18][19] Hence, it has potential application as n-and p-type window layers in organic solar cells due to their excellent physical properties. 5,6 Organic solar cells have attracted much attention because of their low cost and high e±ciency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, boron nanomaterials also have some better properties compared to carbon nanomaterials such as excessive resistance to oxidation at high temperatures and great chemical stability and are stable broad band-gap semiconductor [24,25]. Due to these properties, boron nanomaterials may have great applications at high temperatures or in corrosive environments functioning as supercapacitors, solid lubricants, fuel cells, and batteries [26]. Moreover, the extensive range of boron nanomaterials themselves could be the building blocks for combining with other existing nanomaterials to design and create materials with new properties.…”
Section: Boron Nanotubesmentioning
confidence: 99%
“…[1][2][3][4][5] Additionally, due to a large surface to volume ratio of the inherent nature of nanostructures, ZnO nanorods have been found to exhibit several intriguing phenomena, such as high sensitivity and fast response for the detection of gas molecules 6 and an interesting behavior called photoelastic effect. 7 The photoelastic effect is defined as an external electromagnetic wave capable of producing a change in the internal strain of a material. 8 It is known that ZnO is a good piezoelectric material, 1 in which an electric field can induce a strain and vice versa.…”
Section: Size-dependent Photoelastic Effect In Zno Nanorodsmentioning
confidence: 99%
“…Therefore, an incident light beam is able to induce a change in the internal strain, which leads to the so-called photoelastic effect. 7,8 In this paper, we further explore the characteristic of this interesting property by studying its size dependence in ZnO nanorods. It is found that with decreasing diameter of ZnO nanorods, the magnitude of photoelastic effect increases.…”
Section: Size-dependent Photoelastic Effect In Zno Nanorodsmentioning
confidence: 99%